Analysis of Taxpayer Compliance Levels in The Payment of Motor Vehicle Tax (PKB) at The Samsat Office of Bantaeng Regency - Natasya; M.Ridwan Tikollah; Mukhammad Idrus (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the level of taxpayer compliance in paying Motor Vehicle Tax at the Samsat Office of Bantaeng Regency. The research uses a descriptive quantitative and qualitative approach with data collection techniques through documentation, interviews, and observation. Quantitative analysis is carried out by measuring the formal compliance ratio based on the number of taxpayers who pay on time compared to the number of registered taxpayers, while qualitative analysis is conducted through indicators of awareness, compliance with due dates, compliance with regulations, willingness to pay, and views on Samsat services. The results of the study indicate that the level of taxpayer compliance is relatively high, but it shows a tendency to decrease from year to year. The decrease is influenced by the increasing number of registered vehicles that is not matched by an increase in awareness, the economic factors of the community, and delays in payment due to other priority needs. Service innovations such as mobile services and digital convenience contribute positively, but have not fully encouraged optimal compliance. This study confirms that improving compliance requires continuous education strategies, strengthening public services, and consistent supervision